Potential of hazard mapping as a tool for facing COVID-19 transmission: the geo-COVID cartographic platform - María Jesús Perles Roselló; Juan Francisco Sortino Barrionuevo; Francisco José Cantarero Prados; Hugo Castro Noblejas; Ana Laura De la Fuente Roselló; José María Orellana-Macías; Sergio Reyes Corredera; Jesús Miranda Páez; Matías Mérida Rodriguez (Boletín de la Asociación de Geógrafos Españoles)
The present research analyses the epidemiological bases, the methodology approach and the utility of the Geo-Covid Cartographic Platform to face COVID-19 transmission at an intra-urban scale.  Geo-Covid is based on the study of the main drawbacks and limitations of the current risk maps, and the proposed hazard mapping methodology is presented as an alternative approach with a high spatial-temporal accuracy. It is based on 1) the map of neighborhood active focuses of contagion, which are classified according to several hazard indexes, 2)  the map of highly-transited areas by potential asymptomatic positives cases and 3) the map of Points of Maximum Risk of contagion. In order to test the effectiveness of the proposed methodology for mapping COVID-19 hazard and risk, it has been applied to Málaga City (Spain) during several stages of the epidemic in the city (2020 and 2021). The neighborhood focus of contagion is proposed as the basic spatial unit for the epidemiological diagnosis and the implementation of mitigation and control measures. After the analysis, it has been concluded that the proposed methodology, and thus, the maps included in the Geo-Covid Cartographic Platform allow a realistic and rigorous analysis of the spatial distribution of the epidemic in real-time.